The birth of monotheism: the rise and disappearance of Yahwism - Lemaire, André (Biblical Archaeology Society, 2007)
Before YHWH -- The Origins of Yahwism -- Early Yahwism in Israel's central hill country -- The God of Israel -- Yahwism of the First Temple Period: monotheism or monolatry? -- The divided kingdom and the resurgence of Baalism -- YHWH and his Asherah?: did the God of Israel have a consort? -- Yahwism and aniconism -- The rise of the prophets -- The religious reforms of the Judahite King Hezekiah -- Astral worship and the religious reforms of king Josiah -- The religious crisis of exile -- The emergence of universal monotheism -- Israelite religion in the Persian Empire: YHWH as God of heaven? -- The Temple, the synagogue and Absolute aniconism -- The disappearance of YHWH -- Tetragrammaton YHWH